Effect of the permanent cerebral ischemia on the dentate fascia of the gerbils hypocampus - Liset María García Ariza; Ramón Enrique García Rodríguez (Centro Provincial de Información de Ciencias Médicas, 2019)
A prospective and experimental study was carried out, from the induction of a permanent cerebral ischemic trauma, by means of a cut to the right carotid vein, in 24 gerbils fromMongolia, obtained from theNationalCenterfor Laboratory Animals Production, with the aim of identifying the possible changes in the neurons populations of the hypocampus dentate fascia during ischemia. The results revealed that the permanent cerebral ischemia produces progressive and total destruction of the neurons in the dentate fascia during the first 72 hours of the ischemic process and it shows 3 moments during its course, each of them with specific characteristics, as well as changes in the proportions among the neurons during cellular death, those apparently healthy and those with different quantities of nucleolous in the area damaged by the ischemic process.